Internalization of Qur'anic Values through Huma Betang: Preventive Efforts Against Bullying Behavior - Mahfuz, Taufik Warman; Rahmiatika, Rahmiatika (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
The research explores the philosophy of huma betang in accordance with the Qur'an to prevent bullying. Qur'anic values such as kinship, brotherhood, togetherness, mutual respect, deliberation, justice, and civilized life are found in huma betang. These values prevent bullying, one of the acts that violates social values. Through the wisdom of huma betang, which aligns with the teachings of the Qur'an, understanding and implementing this philosophy can prevent bullying cases and provide a solution to the issue that disturbs the community. The research method used is descriptive qualitative, analyzing data from literature sources such as books, journals, and online media. This study concludes that embracing the values of huma betang can effectively combat bullying behavior.